EFEITOS REPRODUTIVOS DE NANOPARTÍCULAS DE SAIS DE PRATA EM RATOS WISTAR EXPOSTOS DURANTE A PUBERDADE - SLEIMAN, HANAN KHALED (2012)
This study evaluated the effect of daily exposure to nanoparticles of silver salts in the development of pubertal characteristics, serum testosterone and estradiol and interference in organogenesis tissue androgen dependent, daily oral exposure to nanoparticles of silver salts (Ag-NPs). We used three groups of animals, Wistar rats, and tests 1 and 2 were followed to control the 23rd to 90th day of age, receiving the product with silver salts nanoparticles with size of 60 nm and concentration of 0.02 mg / mL by gavage during the period from 23 days until 53 days old. This product has been routinely used as an antiseptic, disinfecting the dentures in deodorants, dental products, among others, and has a characteristic of being possible environmental contaminant. The risks of acute poisoning and / or chronic low doses, may lead the individual to submit pictures of subfertility often undiagnosed. Prepubertal exposure to compounds containing AGNPS negatively influence production and sperm reserves in adults according to the parameters evaluated in this study and ages. Also hormonal changes occur and the development of androgen dependent tissues, age puberty, testicular and morphology. There is need to determine the toxicological levels for this compound both in environmental contamination as directly involved in activities with their routine use in human medicine, since its use can potentially lead to reproductive damage in prepubertal individuals and adults.